Highly iterative concept development for requirement-compliant air taxis. Issue 1 (1st February 2022) - Schuh, G.; Spangenberg, M.; Meyer-Hollatz, T.
Abstract: The increasing demand for individual mobility worldwide is leading to the development of new forms of mobility. Individual air mobility (e.g., air taxis) could be one innovative approach to meet this increasing demand. To successfully realise such innovative approaches, interested companies must know the technical, economic, and ecological requirements of all relevant stakeholders and integrate them in their air taxi developments. Based on these diverse requirements, a resilient air taxi concept must first be created that describes the essential characteristics of future air taxis and enables a well-founded assessment. However, in practice, it is often difficult for companies to outline such a concept and then develop it consistently and highly iteratively. To face this challenge, a process has been set up which creates a deep link between the requirements and concept development phase to assure the development of requirement-compliant air taxis in an agile manner. The process is divided into two parts. The first part connects the market analysis, requirements definition and concept creation, thus linking the requirements and concept development phase. It is based on a double diamond model consisting of two phases. In contrast, the second part is focusing on the pre-development until the end of the concept development phase by adapting the SCRUM methodology to derive a sound air taxi concept. Both parts are executed in a highly iterative manner to reflect the significant amount of uncertainty at this early process stages.